Development of soft skill-based interactive media on thematic learning - Urip Umayah; Gigih Winandika; Defry Azhari; Delly Nofiani (Fakultas Tarbiyah Universitas Ibrahimy, 2023)
An interactive learning strategy was a method or technique the teacher used when presenting learning materials where the teacher became the main actor in creating an educative interactive situation. The objective of this study was to create interactive media for theme learning that focuses on the development of soft skills and to evaluate its quality and usefulness. This study used Borg and Gall's Research and Development (R&D) approach, with four parsimonious stages of development: analysis, design, development, and implementation. This research used observation and interview sheets as data collection methods. The assessment of the interactive media's validity, quality, and efficacy based on soft skills was conducted through instrument and product validation methods involving media specialists and reviews from instructors and students. The study showed that students and teachers rated interactive learning media based on soft skills in the high-quality category. In addition, soft skill-based learning media was considered effective in fulfilling the criteria for assessing teacher activity in learning media, namely in the very effective category. It was concluded that the soft skill-based interactive learning media developed in this study were valid, high quality, and effective, so they were suitable for use in Penggalang 4 public elementary schools. We recommend that schools implement interactive media based on soft skills so that students become active and critical learners. Future research can adapt our model to other educational levels or domains, such as employee business development.